Pengaruh Pemahaman Pajak terhadap Kepatuhan Pelaporan SPT Wajib Pajak Orang Pribadi di KPP Pratama Palembang Ilir Timur - Bayu Satria; Paisal; Yulia Pebrianti (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This study has the aim of looking at the effect of taxes on individual taxpayer SPT reporting compliance at KPP Pratama palembang Timur The object in this study is located at KPP Pratama Palembang with the subject of taxpayers residing in the KPP Pratama Palembang Timur area. This study uses 100 responses, this study including a research descriptive survey that uses a population as a sample which then collects data Using primary data by means of a questionnaire, the analytical techniques used in this study are validity test, reliability test, classical assumption test, simple linear regression test, determinant coefficient test, and t test. Â